Green synthesis, characterisation and biological evaluation of AgNPs using Agave americana, Mentha spicata and Mangifera indica aqueous leaves extract. Issue 5 (1st October 2016) - Ahmad, Bashir; Shireen, Farah; Bashir, Shumaila; Khan, Ibrar; Azam, Sadiq
Abstract : The current study was performed to synthesize stable, eco‐friendly and bio‐compatible silver nano‐particles (AgNPs) of Agave americana, Mentha spicata and Mangifera indica leaves and to screen them for biological activities. The ultraviolet‐visible spectroscopic analysis revealed that λ‐max for AgNPs range from 350–500 nm. All AgNPs possessed polycrystalline structure as notified as intense graphical peaks in complete spectrum of 20 values ranging from 10–80° in X‐ray diffraction measurements and supported by scanning electron microscopy data. The size of the nano‐particles was confirmed by transmission electron microscopy (30–150 nm). Mass loss at variable temperatures was evaluated by simultaneous thermogravimetric and differential thermal analysis revealed reduction in mass and activity of compounds was notified by temperature increase from 200 to 800 °C, thus concluding it as thermally sensitive compounds. A. americana AgNPs showed significant (96%) activity against Methicillin resistant Staphylococcus aureus, Escherichia coli (95%) and Fusarium oxysporum (89%). Good antioxidant activity was shown by M. spicata AgNPs at 300 µl (79%). M. indica AgNPs showed significant phytotoxic activity (88%) at highest concentration. No haemagglutination reaction was observed for the test samples. The above results revealed that AgNPs synthesized from selected plant species possesses significant antimicrobial and phytotoxic effect.